Présence et influence assyriennes dans le royaume de Hamat - Baaklini, Adonice-Ackad, 1988- (Oxford, UK)
xiv, 371 sayfa
Keywords: “The major part of the Near East was conquered by the Neo-Assyrian Empire (934-610BC) in a few centuries. If the geopolitical map of the region was altered, the concrete impact it exerted on the territories with which it came into contact is difficult to appraise. Until recently, there was a general tendency to consider that the Assyrians tightly controlled their whole periphery by maintaining a high number of soldiers and personnel while initiating a process of 'Assyrianization'. Présence et influence assyriennes dans le royaume de Hamat assesses the importance and nature of the Assyrian presence in the kingdom of Hamat (in northwest Syria) to determine whether there is a link between the presence and influence of the Assyrians. The results of an analysis of historical and archaeological sources show that the Assyrian presence in Hamat was much more subtle than what might have been imagined. On the one hand, the Assyrian provincial elite insisted on being legitimized with the natives and cooperating with the local elite rather than using force to maintain the yoke of the Empire. On the other hand, far from indicating Assyrian colonization or a change of culture, the influence of Assyrian culture in Hamat would rather translate into the local elite adopting new objects of prestige that contributed to conspicuous consumption and competitive emulation“ --